Produksi Pesan Dakwah Bil-Kitabah Melalui Ilustrasi Digital - Nurhasanah, Dewi; Sumijaty, Siti; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determine the production process of bil-kitabah da'wah messages through digital illustrations carried out by the Instagram account @Qomikin, by knowing the pattern of content knowledge and the pattern of procedural knowledge of the Instagram account @Qoimikin. The research method used is a case study method with a qualitative approach with a constructivism paradigm. The results showed that the Instagram account @Qomikin in the message production process had content knowledge in producing illustrations containing da'wah messages. In addition, the @Qomikin Instagram account has procedural knowledge that it goes through, namely the pre-production, production, and post-production stages. Thus, digital illustration skills in this era have an important urgency in order to be able to answer the challenges of preaching through written and visual media.